Let f(n)=1+2+3+...+n.
Now, we have f(n)−f(n−1)=n, and we will prove f(n)+f(n−1)=n2 by induction.
Since the proposition is true for n=1, let us assume it is true for n=k. Now for n=k+1, we have: f(k)+f(k+1)=[f(k)+f(k−1)]+2k+1=k2+2k+1=(k+1)2. So, we conclude that f(n)+f(n−1)=n2 for n belongs to N. Now, we have a system of simultaneous equations: f(n)+f(n−1)=n2 f(n)−f(n−1)=n solving them, we have 2f(n)=n2+n which yields:
f(n)=n(n+1)/2
#Algebra
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
or_italics_
**bold**
or__bold__
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
\(
...\)
or\[
...\]
to ensure proper formatting.2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
Comments
I guess you meant f(n)-f(n-1)=n (not 2) at two instances.
Log in to reply
thank you very much!!!
Cool
Log in to reply
thank you very much
How is this proof?
Well I guess that you used the mathematical induction in this problem, right? It's a kind of simple method to prove such these kind of mathematical statements. I like it.
Log in to reply
Thx!!!
Cool proof! @Mohammed Imran
Log in to reply
thank you!
Oh nice, where did you see this?
Log in to reply
this is the original proof of the theorem by gauss
Log in to reply
Then why did you type it as yours?🤔
Log in to reply
Log in to reply
@Brilliant Mathematics, @joan davis has wrote 5 posts that don't relate to mathematics.
Log in to reply
Thank you for notifying us again. We will take action on this shortly.